CHARACTERISTICS OF THE “DEMOGRAPHIC COMPENSATION” IN THE SOUTH OF THE KRASNOYARSK REGION IN THE LATE 1940S-1950S - Barantseva N.A. (Scientific Journal of Pedagogy and Economics, 2020)
The article reveals the specifics of “demographic compensation” of the population of the South of the Krasnoyarsk region in the late 1940s-1950s after the devastating consequences of the Great Patriotic war based on archival material and statistics. The influence of demographic factors on the population’s recovery processes was revealed such as changes in gender and age structure, birth rate, mortality, and marriage. The influence of the socioeconomic situation in the country on the natural movement is shown. The specifics of reproduction of the region’s population among citizens and villagers, various ethnic communities are considered. The use of general scientific and demographic research methods, the regulations of the general theory of population, the concept of “human potential” allowed us to conclude that there is a tendency to overcome the “demographic hole” which was caused by human losses in wartime. The population of the South of the Krasnoyarsk territory has returned to the expanded historical type of reproduction. The practical significance of the results and conclusions of the study eliminates the gaps in the territorial and problem aspects in the historiography of the topic of “demographic compensation” of the Siberian population. The obtained materials can become the basis for studying the local history of the population of other Siberian regions.